Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen